Literasi Digital: Tiktok Sebagai Media Pembelajaran Dalam Meningkatkan Pemahaman Kaidah Bahasa arab - kasmudi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
The use of technology has now penetrated all aspects of life, even in the education process, including Arabic language learning activities. TikTok is a video sharing social networking platform service that is growing quite rapidly. Previous research has stated that the use of TikTok as a medium for learning Arabic is very relevant to current developments. This research aims to find out the content for learning Arabic language rules that is most interesting and most liked by selected users from the hashtags #nahwu and #nahwushorof. The method used in this research is a content analysis method with a qualitative approach. Data collection techniques include observation and documentation. The subjects in this research were four TikTok creators who were selected based on the number of followers, number of likes and based on the content or Arabic learning materials they created. The objects of this research are videos uploaded by four TikTok creator accounts related to learning Arabic language rules and comments or responses from followers of these accounts as well as literature that supports the research. The research results show that there are four Arabic rules learning accounts that are uploaded regarding Arabic rules that are most liked and interested by TikTok users and followers based on audience engagement. The findings of this research can be used as one of the main literacies in learning Arabic language rules.